OECD Employment Outlook 2019 : the future of work - (:unkn) unknown (OECD Publications, 2019)
"The 2019 edition of the OECD Employment Outlook presents new evidence on changes in job stability, underemployment and the share of well-paid jobs, and discusses the policy implications of these changes with respect to how technology, globalisation, population ageing, and other megatrends are transforming the labour market in OECD countries. The report discusses how labour market regulation might be used to extend rights and protections beyond standard employees, as well as to rebalance bargaining power between employers and workers. It analyses how collective bargaining and social dialogue can be mobilised to address emerging challenges in the labour market, looking at the role of government, social partners and new forms of collective organisation. The role of adult learning is also addressed, with a particular focus on the most vulnerable groups. And finally the report also assesses challenges for social protection policies, presenting evidence on the support gaps affecting different types of worker, and discussing reform avenues for preserving and strengthening the key stabilising role of social protection systems." (excerpt ; BIBB-Doku)
Keywords: G 2.3 Wandel von Arbeit & Wirtschaft; G 1.2 Arbeitsmarkt; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.2.2.2 Soziale Sicherungssysteme; Zukunft der Arbeit; Arbeitsmarktentwicklung; Beschäftigungsentwicklung; Einkommensentwicklung; Globalisierung; Technischer Wandel; Digitalisierung; Erwachsenenbildung; Sozialpartner; Sozialversicherung; Soziale Sicherheit; Arbeitsmarktpolitik; OECD-Staaten; Quantitative Angaben